Legal Protection Againts Buyers due to not Performing Seller in Electronic Transaction - Anggraeni, Dewi; Niagara, Serena Ghean; Anwar, Mohammad (International Journal of Economics and Financial Issues, 2018)
Transaction in electronic transaction is a legal action taken used a computer to, computer network, and or other electronic media. Setting the covenant of trading in electronic transaction equal to trading in general, in the book of the act of civil law, act no. 8 / 1999 on consumer protection and the act of no. 11 year 2008 about information and electronic transaction or also called by law ite. Article 1338 (1a book the act of civil law explain if agreement which was built by legally valid as the act of for those who, the agreement applied and binding on the parties legally. But in fact trading online on the implementation of the rights and obligations the parties not according to what promised. What happens not performing that is generally carried out by the seller? Keywords: legal protection, not performing, electronic transaction JEL Classifications: G21, H32, K42